Pollen morphology and its taxonomic significance in Iranian Colchicum (Colchicaceae) - Vahdati, Fatemeh Bazdid; Beygom Faghir, Marzieh; Assadi, Mostafa (Phytotaxa, 2023)
Pollen morphology of 15 species of Colchicum was studied using light microscopy (LM) and scanning electron microscopy (SEM). The results revealed considerable pollen character variation among the studied species, which provides helpful data for species delimitation in Colchicum. The pollen grains are monad, bilateral symmetrical, isopolar to subisopolar, prolate, perprolate, subprolate and oblate spheroidal and medium to large in size. The outline of pollen grains varies from circular to tetragonal from polar view and elliptical from equatorial view; it is dicolpate, tetrazonoporate or diporate. The results showed five types of sexine ornamentation. The current study demonstrates that the pollen morphological characters are significant in taxonomic classification of the Colchicum and provide valuable information for species identification. We performed multivariate analysis to assess the possible contribution of palynological data to the species relationships. The results of cluster and principal component analysis demonstrated a close relationship among the studied species.